Analisis Kualitas Pelayanan dan Kaitannya dengan Minat Kunjungan Ulang Pasien Umum di RS Islam Pondok Kopi Jakarta Timur - Ratu Amalina Ramadhani; Dwi Nurmawaty; Ade Heryana; Namira Wadjir Sangadji (Pusat Riset dan Inovasi Nasional, 2025)
Revisit intention is the tendency of a patient to return to the same healthcare facility after receiving prior services. Based on a preliminary study of ten Out of Pocket patients at RS Islam Jakarta Pondok Kopi, 60% showed low revisit intention. This study aims to determine the relationship between service quality and revisit intention among Out of Pocket patients in the outpatient unit. The research used a quantitative approach with a cross-sectional design. The study population consisted of all Out of Pocket patients from January to April 2025, with a total of 9,664 patients. The sample size was 65 respondents, selected through purposive sampling. Data were collected using questionnaires measuring revisit intention (Behavioral Intention model) and service quality (SERVQUAL dimensions). Data analysis included univariate and bivariate analysis using the Chi-Square test. The results showed that 50.8% of respondents had low revisit intention. The highest dissatisfaction was in the tangibles dimension (60%), while the reliability (56.9%), responsiveness (53.8%), assurance (61.5%), and empathy (63.1%) dimensions were mostly rated as satisfactory. Bivariate analysis revealed significant relationships between revisit intention and all service quality dimensions: tangibles (p < 0.001), reliability (p < 0.001), responsiveness (p < 0.001), assurance (p 0.003), and empathy (p 0.006). Therefore, improvements in all five dimensions of service quality are essential to increase Out of Pocket patients’ revisit intention.